Numerical modeling and analysis of CdS/Cd1-xZnx Te solar cells as a function of CdZnTe doping, lifetime and thickness - Imamzai M.; Aghaei M.; Amin N. (2023)
The main purpose of this paper is to investigate the effect of bandgap, carrier concentration, minority carrier life time and CdZnTe absorber layer thickness on the thin film solar cell baseline case. The bandgap of Cd 1-xZnx Te solar cells are tunable between 1.4SeV and 2.2eV (depends on the value of x). In this research AMPS-1D has been used for simulation. The results of this study indicate that by decreasing the absorber layer's thickness, the efficiency decreases. In the baseline cases, the absorber layer's bandgap was changed from 1.45eV to 2.05eV, It was found out that by increasing the energy gap, efficiency increases but after 1.85ev the bandgap will be constant, hence Eg=1.88eV was considered for absorber to analyze the baseline cases. It was observed that by increasing the lifetime and carrier concentrations of absorber layer, the output parameters increase in the cells. However, the baseline cases structures are the same (SnO 2/CdS/CdZnTe/Back Contact) and the highest conversion efficiency of 25.505% is obtained by baseline case 2 (Jsc= 29.819 mA/cm 2, Voc = 1.28 Volt, FF= 0.731) which has higher doping and minority carriers lifetime. 2013 IEEE.